Doses of noise to whom are subject operators portable harvester coffee - Sales, Ronan Souza; Silva, Fábio Moreira da; Silva, Flávio Castro da (Coffee Science - ISSN 1984-3909, 2015)
The harvest of coffee (Coffea arabica L.) is a costly process that demands high cost labor , increasingly scarce and the mechanization process a way for the farmer to remain in the activity . The objective of this study was to analyze the noise dose to which they are exposed operators portable harvester. The experiment was carried out in a coffee plantation of Catuaí Amarelo 62. For the experiment we used two portable harvester DL271K model and a dosimeter DOS-500 to quantify the noise dose, through by measuring the sound pressure level for each minute. The results lead to the conclusion that the maximum noise level to which they were subjected operators was 94.4 and 95.7 dB(A) for the first and second day respectively and that the noise dose to which they were submitted the operators was 131.6 and 143% for the first and second day, respectively. These values are higher than the limits established by low in Brazil. Can be noted that job security depends on each individual who performs, but the operator should have the right to know the risks they are exposed to while performing their activities.